VOICES FROM THE CLASSROOM: INDONESIAN EFL TEACHERS’ ATTITUDES AND EXPERIENCES TOWARD CULTURAL CONTENT IN STATE-PRESCRIBED TEXTBOOKS - Sofia Uswatunisa; Indah Tri Purwanti; Eliwarti (International Journal of Educational Best Practices, 2025)
Textbooks play a central role not only as instructional resources but also as instruments that shape learners’ in acquire a language and culture. The dominance of national culture in locally produced EFL textbooks, coupled with the neglect of target-language and multicultural elements, highlights significant issues concerning teachers’ attitudes and their responses to cultural representation during instruction. This study aims to analyze teachers’ attitudes and experience on EFL textbooks on English teachers in SMPN Pekanbaru. The research was conducted from April to July 2025 with descriptive quantitative and thematic analysis. A total of 50 English teachers were selected as respondent trough purposive sampling. Data analysis was conducted using SPSS 23 ver. The result showed that comfort with cultural content increases when textbooks provide culturally rich, engaging, and contextualized examples. Besides, low affective responses are often linked to the perceived of nature culture in the textbooks. According to teachers’ experiences, overly familiar or monotonous stories often do not maintain students’ engagement. Moreover, teachers found students responded more positively to culturally unfamiliar stories compared to local or overly familiar one. The implication of this study emphasizes the significant space for improvement, particularly in the balanced inclusion of cultural dimensions that foster both local identity and global awareness and it is recommended that government-issued EFL textbooks be revised to reflect a balanced integration of source, target, and international cultures. Teachers encouraged critically adapting materials and pursuing professional development in intercultural competence.